2021
DOI: 10.1186/s13244-021-01021-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle elasticity is different in individuals with diastasis recti abdominis than healthy volunteers

Abstract: Objective To determine the value of shear wave elastography (SWE) in assessing abdominal wall muscles, including rectus abdominis (RA), external oblique muscle (EO), internal oblique muscle, and transversus abdominis (TrA) in patients with diastasis recti abdominis (DRA) and healthy controls. Methods From October 2018 to December 2019, 36 postpartum DRA patients and 24 nulliparous healthy women were identified. Inter-rectus distance (IRD) measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The IRD, thickness, and Young's modulus of rectus abdominis were different at different gestational periods. The two-dimensional morphological changes are inversely related, that is, as IRD widened with the progression of pregnancy, the thickness of the rectus abdominis decreased, and the Young's modulus of the rectus abdominis elasticity decreased accordingly, namely, reduced elasticity of the rectus abdominis, which is similar to the results of He et al, 7 who found that the SWS value of rectus abdominis in patients with DRA decreased significantly. This may be due to the biomechanical and pathological changes in muscle fibers with the increase in the IRD.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The IRD, thickness, and Young's modulus of rectus abdominis were different at different gestational periods. The two-dimensional morphological changes are inversely related, that is, as IRD widened with the progression of pregnancy, the thickness of the rectus abdominis decreased, and the Young's modulus of the rectus abdominis elasticity decreased accordingly, namely, reduced elasticity of the rectus abdominis, which is similar to the results of He et al, 7 who found that the SWS value of rectus abdominis in patients with DRA decreased significantly. This may be due to the biomechanical and pathological changes in muscle fibers with the increase in the IRD.…”
Section: Discussionsupporting
confidence: 83%
“…The IRD, thickness and Young's modulus all change during different gestational periods, and the decrease in muscle thickness and fiber volume of gravidas can lead to the slow propagation speed of SWE. 7 Therefore, the correlation analysis in this study showed that the Young's modulus of rectus abdominis had a certain relationship with IRD and thickness of rectus abdominis, but had no significant correlation with neonatal weight or delivery mode.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The rectus sheath wraps the rectus abdominal muscles and is divided into two layers: the anterior is formed by the healing of the aponeurosis of the external oblique muscle and the aponeurosis of the internal oblique muscle, and the posterior rectus sheaths are formed by the healing of the aponeurosis of the internal oblique muscle and the aponeurosis of the transverse abdominis. The posterior rectal sheath is functionally more related to transverse abdominis than rectus abdominal muscles, and activation of transverse abdominis plays an important role in the etiology of the DRA ( 34 , 35 ). Physical exercises adopted in this study, such as left and right-side leg rotation, are more effective in activating deep transverse abdominis, external oblique muscle, and internal oblique muscle ( 36 , 37 ), and posterior rectus fascia sheath formed by transverse abdominis tendon sheath has better efficacy in maintaining abdominal wall tension stability.…”
Section: Discussionmentioning
confidence: 99%
“…In physiotherapy, conventional ultrasound imaging (USI) is commonly used for non-invasive measurement of the inter-recti distance (IRD) [1,2], and pregnancy-related diastasis recti abdominis (DRA) when assessing, for example, the effectiveness of postpartum physical exercises [3,4,5,6]. Desings of these studies usually require IRD measurements with USI in both pregnancy-related DRA subjects and nulliparous controls [7,8,9]. The increasing popularity of this assessment method raises the issue of IRD measurement repeatability and reliability using ultrasonographic imaging, and the importance of the examiner's experience.…”
Section: Introductionmentioning
confidence: 99%